OPTIMALISASI PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Rodliyah, Rodliyah (Jurnal Media Hukum, 2012)
Domestic Violence Crimes (Domestic Violence) is a social phenomenon that often occurs in the community and the victims are mostly women. It is not only a national problem but an international problem, so set some instruments of international law and national legal instruments are adequate, which should be legal protection for women victims of domestic violence in the legal process can be catered for. In real terms the legal protection of women victims of domestic violence is still very weak, with an indication of the number of reports that were not followed up to the stage of the investigation, due to various constraints both in the community and from law enforcement officials. Optimization measures are needed legal protection for women victims of domestic violence, such as the high commitment or spirit of the law enforcement agencies to tackle domestic violence, meets all the rights of victims, providing legal aid to victims of the maximum judicial process, increase public awareness that domestic violence is a crime , not just a personal issue that no intervention, the offender must be processed to provide a sense of security to the victim and her family.Key words: Protection, Women, Violence